ISLAMIC PAWNING IN PEGADAIAN SYARIAH: EVALUATING THE IJARAH CONTRACT IN ACCORDANCE WITH PSAK 107 - Rosna Melly Agustin; Muhammad Dzikri Hurobbani; Metiya Fatikhatur Riziqiyah (UIN MAHMUD YUNUS BATUSANGKAR, 2026)
The implementation of sharia pawn in Pegadaian Syariah is one form of financing product development based on sharia principles through the use of rahn contract as collateral and ijarah contract as the basis for determining service imbalances. In practice, the separation between rahn and ijarah contracts is important so that the ijarah contract remains understood as an independent service contract and does not shift to become part of the financing mechanism. This also has applications in accounting treatment that must refer to PSAK 107 concerning Ijarah Contracts. This study aims to analyze the implementation of ijarah contracts in sharia pawn using PSAK 107 as a normative evaluation framework. The research method used is a descriptive qualitative approach based on literature studies with data collection techniques through reviewing various sources such as PSAK 107, DSN-MUI fatwas, regulations, and related literature. The results of the study indicate that the conceptual implementation of the ijarah contract in Islamic pawnshops has referred to PSAK 107, particularly regarding the contract object in the form of services, contract discounts, and revenue recognition based on service benefits. However, there are still potential discrepancies, especially in the determination of ujrah and the clarity of contract clarification in conceptual practice. This study confirms that PSAK 107 functions not only as an accounting standard, but also as a tool for evaluating the suitability of the implementation of the ijarah contract in Islamic pawnshops.